Experience in rural labor restructuring in some countries around the world and reference lessons for Vietnam - Truong, Doan Van (Linguistics and Culture Review, 2021)
Promote restructuring of rural workers has very important implications in the development of the potentials and strengths of the economy. Vietnam is a country with a starting point from agriculture, a large proportion of GDP. In recent years, although there has been a positive change in transformation, the process is still slow. To have a reasonable labor structure shortly, Vietnam can completely refer to the experience of several countries in the world with similar starting points. The article analyzes lessons learned from rural labor restructuring in some countries around the world, from which to draw reference lessons for Vietnam.